FEATURES OF USING A CONCEPTUAL TERMINOLOGICAL DICTIONARY IN THE TRAINING OF FUTURE COMPUTER SCIENCE TEACHERS - Bidaibekov, Е.Ы.; Rakhymbek, Н.Ж.; Zhaidakbayev, Л.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article discusses the features of the use of the conceptual and terminological dictionary in the training of future computer science teachers. The experiment was conducted at the South Kazakhstan University named after M. Auezov, on the basis of the South Kazakhstan Pedagogical University. The methodology and methods of organizing and conducting practical work on teaching a conceptual and terminological dictionary in the training of future computer science teachers are described. The analysis of the results of experimental work is presented graphically in the form of tables, diagrams. The pedagogical experiment was carried out in three stages: determining, formative, and final. At the stages of experimental work, the following research methods were used: analysis, generalization, systematization, observation, survey, testing, research and generalization of pedagogical experience. As a result of the experimental work, the results of the control group and the expert group were analyzed. As a result, students of the experimental group can see an increase in theoretical knowledge in mastering the ICT course in English. This circumstance leads to an increase in the competence of the teacher, the use of conceptual terminological terms in the AKT course in the training of future computer science teachers.